Peran Pemimpin Dalam Meningkatkan Kinerja Pegawai Dinas Perhubungan Kota Samarinda - Roland Karina Lumban Toruan; Jamiah Jamiah; Diana Diana (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2021)
This type of research is to determine and describe the role of the principal in improving This research is motivated by a problem where the influence of the role of the leader in the Office of Transportation of the City of Samarinda has not run optimally in improving employee performance. The role of the leader is highly expected so that employees are directed and professional, making it easier to achieve a goal to be achieved together, employees are still less disciplined in carrying out work and there are still employees who are not on time when they leave the office. As a leader, he must be able to improve employee performance by providing motivation, encouragement and directing employees to realize the vision and mission of the Samarinda City Transportation Office. The results showed that the role of the Deputy Head of the Samarinda City Transportation Service in improving the performance of employees at the Samarinda City Transportation Service office carried out its role as a Personal Role, Information Role and Decision-Making Role in improving employee performance at the Samarinda City Transportation Office.Penelitian ini berlatar belakang oleh sebuah masalah dimana pada pengaruh peran pemimpin di kantor Dinas Perhubungan Kota Samarinda belum berjalan dengan maksimal dalam meningkatkan kinerja pegawai. Peran pemimpin sangat diharapkan agar para pegawai terarah dan profesional, sehingga lebih mudah untuk mencapai suatu tujuan yang ingin dicapai bersama, pegawai masih kurang disiplin dalam melaksanakan pekerjaan dan masih ada pegawai yang tidak tepat waktu pada saat turun kantor. Selaku pemimpin harus bisa meningkatkan kinerja pegawai dengan memberikan motivasi, dorongan dan mengarahkan pegawai untuk mewujudkan visi dan misi kantor Dinas Perhubungan Kota Samarinda. Hasil Penelitian menunjukkan bahwa Peran Wakil Kepala Dinas Perhubungan Kota Samarinda dalam meningkatkan kinerja pegawai pada kantor Dinas Perhubungan Kota Samarinda menjalankan perannya sebagai Peranan Pribadi, Peranan Informasi dan Peranan Pengambilan Keputusan dalam meningkatkan kinerja pegawai pada kantor Dinas Perhubungan Kota Samarinda.